Studi Tuberkulosis Kontak Serumah pada Masyarakat Pesisir di Wilayah Kerja Puskesmas Siko Kota Ternate - Erpi Nurdin; Irma B. Hi. Lewa; Mukhtasyam Zuchrullah (Jurusan Biologi Universitas Negeri Makassar, 2022)
Pulmonary tuberculosis is still the main cause of death in the world, accounting for 2 million people die every year. WHO states that around 1.9 billion people, one third of the world's population, have been infected with tuberculosis germs, every second one person is infected with tuberculosis in the world. Pulmonary tuberculosis is transmitted through droplet spread with the source of infection being patients who are coughing with household contacts as a high risk group for transmission. To find out the results of the examination and see the percentage of positive or negative acid-fast bacilli (AFB) in a sample of clients who have a history of household contact with patients with pulmonary tuberculosis. This study uses a with correlation approach research method with an observational approach. The sampling technique is purposive sampling, namely sampling based on the considerations of the researcher. The examination method used was the Zielh Nelseen method of 30 sputum samples examined. From 30 respondents, 4 respondents were found positive for microscopic acid-fast bacilli (AFB). 2 positive family members, have the characteristics of dense housing (not eligible), humidity and ventilation do not meet the requirements, but the type of floor still meets the requirements. Based on the research that has been carried out, it is concluded that 4 (13%) respondents were identified as positive for scanty with the presence of tuberculosis in 3 places of tuberculosis in household contacts, with factors that influence the occurrence of tuberculosis in household contacts. There is no significant relationship between the results of AFB examination and gender (p value = 0.407> 0.05). There is no significant relationship between the results of AFB examination and age (p value = 0.272> 0.05).